2017
DOI: 10.1016/j.jclinane.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parecoxib sodium pretreatment combined with dexmedetomidine on early postoperative cognitive dysfunction in elderly patients after shoulder arthroscopy: A randomized double blinded controlled trial

Abstract: Study objectiveTo evaluate effect of parecoxib sodium pretreatment combined with dexmedetomidine on early postoperative cognitive dysfunction in elderly patients after shoulder arthroscopy.DesignRandomized, double-blind study.SettingUniversity-affiliated teaching hospital.PatientsOne hundred and fifty-two elderly patients scheduled for shoulder arthroscopy.InterventionsAt 15 min before the induction of anesthesia, 152 patients received intravenously parecoxib sodium 40 mg and dexmedetomidine at a dose of 0.5 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
(23 reference statements)
1
46
0
Order By: Relevance
“…These ndings are compatible with the results of our study that dexmedetomidine has no effects on postoperative cognitive function in elderly patients anaesthetized with remifentanil and propofol. Several studies have demonstrated that dexmedetomidine may bene t cognitive function in elderly patients due to its neuroprotective effect and inhibiting inflammation 24,26,27 . In our study, we didn't detect the Plasma in ammatory factors, and the effect of dexmedetomidine on plasma in ammatory mediators in elderly patients was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings are compatible with the results of our study that dexmedetomidine has no effects on postoperative cognitive function in elderly patients anaesthetized with remifentanil and propofol. Several studies have demonstrated that dexmedetomidine may bene t cognitive function in elderly patients due to its neuroprotective effect and inhibiting inflammation 24,26,27 . In our study, we didn't detect the Plasma in ammatory factors, and the effect of dexmedetomidine on plasma in ammatory mediators in elderly patients was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We didn't detect the Plasma in ammatory factors in our study. Many studies have reported that the protective effect of dexmedetomidine on cognitive function due to its inhibiting inflammation [24][25][26] . The patients selected in our study had almost no postoperative pain, so the effects of remifentanil-propofol combined with or without dexmedetomidine on cognitive dysfunction in elder patients with postoperative pain were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The authors performed a prospective randomized study on 60 patients undergoing hallux valgus surgery and concluded that ankle block added to general anesthesia may improve early and mid-term postoperative functional outcomes and postoperative pain management in patients who undergo hallux valgus surgery. The authors should be congratulated for performing a study on an important topic in patients undergoing orthopedic surgery [2]. Moreover, the current emphasis on the need to use nonopioid strategies to improve postoperative pain makes the subject very relevant to perioperative medicine [3,4].…”
Section: Dear Editormentioning
confidence: 99%
“…1 Postoperative cognitive dysfunction (POCD) has attracted extensive attention, which generally manifests as amentia, anxiety, personality changes, sociability decline, and memory impairment. 1 Postoperative cognitive dysfunction (POCD) has attracted extensive attention, which generally manifests as amentia, anxiety, personality changes, sociability decline, and memory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has severely affected the postoperative recovery and health of patients. 1 However, the precise mechanism of action of POCD remains unclear at present, and the aged patients have more severe POCD. 3 The incidence within 1 week and 3 months after surgery are as high as 47.3% and 6.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%